2011
DOI: 10.1001/dmp.2011.63
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Laboratories and Radiological Readiness

Abstract: ABSTRACTObjective: To document the ability of public health laboratories to respond to radiological emergencies.Methods: The Association of Public Health Laboratories developed, distributed, and analyzed two separate surveys of public health laboratories representing the 50 US states and major nonstate jurisdictions. The 2009 All-Hazards Laboratory Preparedness Survey examined overall laboratory capability and capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Only 17 (33%) of 51 respondents to the 2009 survey reported any ability to measure radionuclides in clinical specimens, and 3 (6%) of these indicated that a state agency or department other than the public health laboratory was responsible for testing. The 2011 Radiation Capability Survey solicited responses from environmental, agricultural, and public health laboratories in all 50 states, the District of Columbia, and Puerto Rico and reached similar conclusions 3. Just 26% of respondents reported the capability to test urine specimens for radionuclides, and only 14% reported the capability to test other clinical specimens.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…Only 17 (33%) of 51 respondents to the 2009 survey reported any ability to measure radionuclides in clinical specimens, and 3 (6%) of these indicated that a state agency or department other than the public health laboratory was responsible for testing. The 2011 Radiation Capability Survey solicited responses from environmental, agricultural, and public health laboratories in all 50 states, the District of Columbia, and Puerto Rico and reached similar conclusions 3. Just 26% of respondents reported the capability to test urine specimens for radionuclides, and only 14% reported the capability to test other clinical specimens.…”
mentioning
confidence: 79%
“…The articles by Dainiak et al12 and survey report by Latshaw et al3 that appear in this issue of Disaster Medicine and Public Health Preparedness address the state of US preparedness for radiological and nuclear emergencies and should prompt deliberation about what can be done to improve it. Radiological and nuclear emergencies occur infrequently but have been associated with both immediate and long-term health consequences and psychological distress in affected populations 4567.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sample preparation and data collection take substantial time from laboratory analysts and they are limiting factors for achieving rapid turnaround and high throughput analytical results. In addition to expertise shortage (The National Academies Press, 2012; Latshaw et al, 2011; Ware, 2002; Warwick et al), the technical difficulties and required financial resources for establishing and maintaining a radio-analytical laboratory are also limiting factors for achieving the needed capacity for emergency response to a radiological or nuclear incident. While gamma-ray analysis requires expertise, utilization of a portable analytical system will help to achieve the needed rapid turnaround and high throughput laboratory grade analytical results if the analytical system is built with such features that it allows field personnel to perform sample preparations and data collections.…”
Section: Introductionmentioning
confidence: 99%